2021
DOI: 10.1088/1367-2630/abd9e6
|View full text |Cite
|
Sign up to set email alerts
|

Resource conversion between operational coherence and multipartite entanglement in many-body systems

Abstract: We establish a set of resource conversion relationships between quantum coherence and multipartite entanglement in many-body systems, where the operational measures of resource cost and distillation are focused. Under the multipartite incoherent operation, the initial coherence of single-party system bounds the maximal amounts of corresponding operational entanglement in an arbitrary bipartite partition as well as the genuine multipartite entanglement (GME) in many-body systems. Furthermore, the converted mult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Quantum coherence is not only a manifestation of the superposition principle of quantum states, but also a crucial feature of quantum mechanics. It has been shown that coherence can be regarded as a physical resource , similar to entanglement [36][37][38][39][40][41][42]. One of the main challenges of quantum coherence theory is to find effective methods to capture the dynamics of coherence.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum coherence is not only a manifestation of the superposition principle of quantum states, but also a crucial feature of quantum mechanics. It has been shown that coherence can be regarded as a physical resource , similar to entanglement [36][37][38][39][40][41][42]. One of the main challenges of quantum coherence theory is to find effective methods to capture the dynamics of coherence.…”
Section: Introductionmentioning
confidence: 99%
“…Both quantum coherence and entanglement are crucial physical resources in quantum information processing [1][2][3]. It was shown that quantum coherence and entanglement can be interconverted in bipartite and multipartite systems under certain conditions, which provides an operational connection between these two kinds of quantum resources [4][5][6][7][8][9]. Moreover, operational methods for other resource conversions concerning nonclassicality, quantum correlation, and nonlocality were also put forward [10][11][12][13], and experimental explorations have been demonstrated in the optical and superconducting systems [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable to explore the operational connection between block coherence and entanglement from the viewpoint of experimental operations, although the resource conversion between quantum coherence and multipartite entanglement was investigated [9]. Recently, an operational method was proposed to convert block coherence to bipartite entanglement via a bipartite block-incoherent operation [28].…”
Section: Introductionmentioning
confidence: 99%
“…In many-body quantum systems, the ground state can be in different phases at zero temperature [4], and the MQC is an effective tool to characterize the properties of quantum phases [12][13][14][15][16][17][18][19][20][21][22]. Entanglement monogamy in multipartite systems means that quantum entanglement cannot be freely shared among different subsystems [23] and the quantitative monogamous relations can be used to constitute the measures or indicators for genuine MQC [24][25][26][27][28][29][30][31][32][33][34][35]. Utilizing the tripartite quantum correlation based on the monogamy relation of negativity [27,36], Rama Koteswara Rao et al studied the ground state of quantum transverse Ising model in a fixed triangular configuration via the nuclear magnetic resonance (NMR) system [37].…”
Section: Introductionmentioning
confidence: 99%